Prevalence of feline immunodeficiency virus and feline leukaemia virus in domestic cats in Hungary - Szilasi, Anna (JFMS Open Rep, 2019)
OBJECTIVES: Feline immunodeficiency virus (FIV) and feline leukaemia virus (FeLV) are retroviruses affecting cats worldwide. The objectives of the study were to estimate the prevalence of these retroviruses in domestic cats in Hungary and to characterise the phylogenetic relationships of FIV strains. METHODS: A total of 335 anticoagulated whole-blood samples obtained from both a healthy and ill cat population were examined for the presence of FIV and FeLV with two methods: ELISA and PCR. Statistical analysis was carried out to analyse the data obtained. Sequencing and phylogenetic analysis of partial polymerase (pol) gene sequences was performed to describe circulating FIV subtypes. RESULTS: Statistical analysis showed 11.8% and 9.9% true prevalence of FeLV and FIV, respectively, with ELISA. The apparent prevalence calculated from the PCR results were 17.3% for FeLV and 13.1% for FIV. Phylogenetic analysis of partial pol gene sequences obtained from 22 FIV strains showed that all observed Hungarian strains belonged to FIV subtype B. The strains were grouped into several monophyletic subgroups reflecting the geographic locations of the origin of the samples. The overall mean genetic similarity between the analysed strains was 98.2%. CONCLUSIONS AND RELEVANCE: We report the first thorough overview of the prevalence of FeLV and FIV in Hungary, which is relatively high, and give insight into the genetic diversity of Hungarian strains of FIV.